Rapid Assessment and Classification for Seismic Damage of Mountain Tunnel Based on Concentric Circle Method - Hua Xu; Jingsong Xu; Runfang Sun; Hefu Pu; Yin Cheng (Shock and Vibration)
Concentric circle method (CCM), a new method based on analytic hierarchy process (AHP) and numerical discretization of 40 mountain tunnels damaged by Wenchuan earthquake in China, is proposed to rapidly assess the seismic damage level (SDL) of mountain tunnels. The new method consists of four components. First, according to the type and degree of seismic damage of tunnel, the whole tunnel is divided into a number of successive sections. Second, four factors (i.e., slope and portal damage, lining damage, pavement damage, and earthquake collapse) are selected as the main controlling factor set, and then multilevel factor sets are proposed to establish the assessment system. Third, the discretized assessment indexes and classification criteria are established for the rapid assessment of SDL of mountain tunnel. Finally, based on the comprehensive analysis on the SDL of each section, the SDL of the whole tunnel is calculated in terms of the seismic damage index and synthetic radius. With the assessment results shown on a straightforward concentric circle diagram, the proposed CCM method can rapidly and reliably assess the SDL of mountain tunnel to win over precious time for emergency rescue and provide references for the repair of damaged tunnel. In addition, the accuracy and applicability of the proposed method is verified by using a case study of Longxi tunnel located at the epicenter of the Wenchuan earthquake in China.